KEDUDUKAN HUKUM UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS TERHADAP PERSAINGAN USAHA TIDAK JUJUR - Muhammad Ferdian (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2019)
The Government in the published Act No. 20 Year 2016 about Brands And Geographical Indications one of which had the purpose of providing legal certainty for the community, in the event of a violation-a violation of the trademark made by businessmen who run businesses compete with dishonest with how to imitate (equated in whole) or mepalsukan (equated that substantially/presence of similarities) can be given criminal sanctions in accordance with the provisions of article 100 and article 101. Implicitly the existing regulation currently provides legal protection directly for businessmen who brand its trade name used by dishonest business competition. The Act only provides criminal sanctions of imprisonment and/or fines need for sanctions and fees in the form of closure for business pelalaku businesses that conduct violations in carrying out its business activities related to trademarks. In order to restore the good name of the product that are imitated and counterfeited by the dishonest business competitors as well as the need for regulation that governs the law firmly and fair for businessmen who do not register its trade name brands, so there is no occurrence of impersonation and trademark counterfeiting.